Physical Activity Related to Random Glucose Levels in Adult Patients in Yogyakarta: A Case-Control Study - Nuraisyah, fatma; Rokhamayanti, Rokhamayanti; Irjayanti, Apriyana; Irmanto, Maxsi (Jurnal Ilmiah Kesehatan (JIKA), 2026)
High blood sugar levels are a sign of impaired metabolism in the body. High blood sugar levels with clinical symptoms are the cause of type 2 diabetes mellitus. The aim of the study was to determine the risk factors for blood sugar levels based on community participation through early detection and monitoring of the main risk factors for non-communicable diseases at POSBINDU in the city of Yogyakarta. Data were obtained from the Non-Communicable Disease Information System (NCD-IS) of the Yogyakarta City Health Office in January - June 2022. The study was conducted with a case-control study (cases to controls ratio 1:2) with matched by sex and age group. Cases are people who have blood sugar levels ≥200 mg/dL as many as 169 people. Controls were people with blood sugar levels <200 mg/dL, with a total of 338 people. The analytical test used was the Chi-square test. Physical activity was significantly associated (p-value 0.009; 95% CI 0.55 – 0.91). There is a relationship between lack of physical activity and with the incidence of abnormal blood sugar levels. Lack of physical activity affects blood sugar levels to be abnormal.